Social insurance in the Second Republic of Poland. Social advantage or the policy of caution - Chylak, Karol (Studia Historiae Oeconomicae, 2015)
Social insurance was conceived from a great thought of the social caution, from the thought of protection of an uncertain future. That thought of caution, during the time of development of social insurance, was implemented by the public entities on the one hand and by the civil activity on the other one. However, the process of creation of the social insurance system in Poland did not represent the policy of caution executed by the state. The only sign of caution could be seen with reference to the insurance associations as there the participants decided whether to enter the system or not whereas the state executed the policy of giving privileges to the certain social groups.